Pengaruh Struktur Modal, Ukuran Perusahaan dan Agency Cost Terhadap Financial Distress Pada Perusahaan Sub Sektor Otomotif Periode 2020-2024 - Aldi Setiawan; Ina Liswanty; Emi Masyitah (ProBisnis : Jurnal Manajemen, 2025)
This study aims to determine the effect of capital structure, company size, and agency costs on financial distress in companies in the automotive sub-sector during the 2020-2024 period. This study employed quantitative research. Secondary data sources were used. The population consisted of 10 companies, with a sample size of 50. Data analysis techniques used included descriptive statistical analysis, classical assumption tests, hypothesis testing, and coefficient of determination tests. Based on the partial t-test results, it can be seen that capital structure does not significantly influence financial distress, with a calculated t-value of -1.174 < 2.012. Furthermore, company size does not have a positive and significant effect on financial distress, with a calculated t-value of -1.737 < 2.012. Agency costs do not have a positive and significant effect on financial distress, with a value of -1.737 < 2.012. Based on the simultaneous test, the calculated F value is 75.490 with a significance level of 0.000. If calculated F > F table, there is a significant influence between X1, X2, and X3 on Y.